THE MAIN FEATURES OF THE EVOLUTION OF THE COMPLEX SENTENCES - Nasimi, Garash (SWorldJournal, 2023)
In the research work, the development path of the subordinate complex sentence in the modern Azerbaijani language from the earliest times to the modern level of the language was involved in the study As a result of research, it has been clarified that se